Root Studies of Kim Grass (Vetiveria Zizanioides) in Relation to Soil Conservation in Red and Black Soils of Bundelkhand Region - Nitant, H.C.; Tiwari, R.K.; Tiwari, S.P. (Journal of Soil and Water Conservation, 2022)
The nature of rainfizll, topography of tract and soil type lead to considerable runoff and soil loss. It is reported that about 70% of total geographical area of Bundelkhand region suffers front varying degrees of erosion hazards. Therefore, suitable soil conservation measures are required to control erosion and to achieve higher yields and productivity in the region. Soil and water conservation measures fall into three classes viz., mechanical, agronomical and vegetative. Grasses, however, have been found effective in protecting the soil from erosion hazards. Investigations carried out to study the soil conservation properties of some grasses (Vetiveria zizanioides, Saccharum nzuttja and Heteropogon contortus) growing on red and black soils in Research Farm of Central Soil and Water Conservation Research and Training Institute, Research Centre, Dada. Highest production (164 q/ha) of above ground biomass was obtained in Vetiveria. Also it (Vetiveria zizanioides) exhibited the nzaxinzum mot spread followed by Saccharum munja and Heteropogon contor- tus. Thus more root biomass added to soil (30 cm depth) came to 8576 kg/ha in case of Vetiveria than Saccha•um (8200 kg/ha) and Heteropogon (2476 kg/ha). The higher root biomass in Vetiveria may be due to existence of major part of roots (68% and 17%) in the tipper 0-20 and 0-30 cm soil profile, respec- tively Significant differences in the soil binding capacities of roots of gras- ses were noted. Vetiveria zizanioides, however, gave the maximum value of soil binding factor (W/r2) viz., 335.0 followed by 284.0 Saccharuin munja and 192.3 Heteropogon contortus. (Key word: Conservation Grass, Soil and Water conservation).